Possibility of reviving the nuclear deal with IranAn Analytical Framework for the Iranian Nuclear Negotiations (Damascus University Journal for the economic and Political sciences, 2025)
The Iran nuclear deal, signed in 2015, was considered a major shift in the framework of the Iranian nuclear negotiations, according to which Iran reduced its nuclear facilities and agreed to the Additional Protocol of the International Atomic Energy Agency, in order to lift all economic sanctions that related to nuclear activity. More importantly, it indicated that a mutual Iranian nuclear deal for limiting Iran's nuclear program is possible.After the United States withdrew from the deal in 2018, and with the change of the American administration, the process of multilateral negotiations is still underway in order to revive the Iranian nuclear deal. The research examined the possibility of reaching deal in the current international negotiations to revive the Iranian nuclear deal, through an analytical framework for these negotiations according to the approach of negotiation analysis. Where the Zone of possible agreement (ZOPA) and the ripeness in these negotiations were studied.
Keywords: Iran; USA; Negotiation Analysis; Zone Of Possible Agreement (ZOPA); Nuclear Deal; Ripeness; Deal Design; Mutually Hurting Stalemate (MHS); Way Out (WO)